Statistical energy analysis for vibro-acoustic coupled system with fuzzy parameters. Issue 2 (16th April 2018) - Wang, Yue; Wu, Di; Wang, Lei; Wang, Xiaojun
Abstract : Purpose: This paper aims to propose a novel statistic energy analysis method with fuzzy parameters to study the dynamic and acoustic responses of coupled system with fuzzy parameters, which can expand the applied range of statistic energy analysis method in engineering to some extent. Design/methodology/approach: On the basis of the property of membership level, the uncertain fuzzy parameters are expressed as the interval forms. Interval mathematics and interval expansion principle are adopted to solve the problem with interval parameters. At last, two numerical examples, which include a two-plate coupled system and a single-partition sound-insulation system, are carried out to demonstrate the feasibility and validity of the presented method. Findings: Interval mathematics and interval expansion principle are adopted to solve the problem with interval parameters. Originality/value: By integrating the interval analysis, optimization technique and Taylor expansion method, two non-probabilistic, set-theoretical statistical energy analyses are proposed for predicting the dynamical and acoustical response of the complex coupled system with uncertain parameters in high-frequency domain.